Covid-19 : A View from the Margins - Jain, Yogesh,; Nabia, Sarah, (Brill | Manohar Publishers & Distributors, 2022)
The cataclysmic impact of COVID-19 exposed cracks in India's health and social systems on a scale never seen before. While the pandemic left no one untouched, it disproportionately affected people at the margins and put to test our centuries-old administrative, health, judicial, and social structures. This work is the first attempt to dissect the impact of the pandemic across various axes of marginalization - geography, financial, caste, gender, and religion, to name a few. At its core, this book is the culmination of the stories, experiences, and reflections on inequity as seen and interpreted by 37 sets of authors who responded to the pandemic in their roles as scientists, doctors, administrators, economists, legal advisors, journalists, public health practitioners, and health activists. These stories are the people's history of COVID-19 in India, an archive of memories and lessons crucial to building more resilient, equitable, and just systems in the post-COVID era.